Clinical and hematological relevance of JAK2 V617F and CALR mutations in BCR-ABL-negative ET patients. Issue 10 (26th November 2017) - Limsuwanachot, N.; Rerkamnuaychoke, B.; Chuncharunee, S.; Pauwilai, T.; Singdong, R.; Rujirachaivej, P.; Chareonsirisuthigul, T.; Siriboonpiputtana, T.
ABSTRACT: Background: Classical BCR-ABL1 -negative myeloproliferative neoplasms (MPNs) including polycythemia vera, essential thrombocythemia (ET), and primary myelofibrosis frequently harbor JAK2, MPL, and CALR somatic mutations. Methods: AS-PCR for JAK2 V617F, pyrosequencing for MPL W515L/K, and PCR-fragment analysis for CALR exon 9 mutations were established to analyze genomic DNA isolated from peripheral blood samples of 58 newly diagnosed ET patients in Thailand. Results: JAK2 V617F was detected in 41 patients (71%) and CALR exon 9 mutation was positive in eight patients (14%), whereas no mutation of MPL W515L/K was observed in this study. Patients with CALR mutation were older ( p = 0.023) and exhibited lower number of platelet count ( p = 0.041) than patients without CALR mutation. Two previously known CALR mutation types were identified in this study (six patients with CALR -type 1 and two patients with CALR -type 2). Additionally, no co-existence of JAK2 V617F and CALR mutations was identified in this work. Conclusion: We reported the frequency of JAK2 V617F, MPL W515L/K, and CALR mutations in Thai patients with ET. Clinical and hematological phenotypes of patients were associated with JAK2 and CALR mutation statuses. The combination of laboratory testing for the detection of JAK2, CALR, and MPL mutations is necessary to improve the diagnosis and classification of BCR-ABL1 -negative MPN.